The Impact of the Discourse on the Village Head's Term of Office for 27 Years on Village Financial Management - Rizky Octa Putri Charin (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
Indonesia started its new year by facing demands from thousands of Village Heads, the demands that were filed were a discourse on extending the term of office of the Village Head from 6 years to 9 years for 3 periods with a total term of office is 27 years. This research more specifically will discuss the impact that will have on the discourse of 27 years of Village Head office proclaimed by the Association of Indonesian Village Governments (APDESI) in January 2023. The theory used in this research is the CDMA theory put forward by Robert Klitgaard (1998) consists of four main elements: corruption, democracy, market, and administration. This research is a single instrumental case study. The cases that will be comprehensively analyzed are the discourse on the 27-year term of office of the Village Head and the implications for village financial management. Then the researcher used Lingga District, Riau Island Province as a case to develop a detailed description of the case. The findings in this study are if the discourse on the 27-year term of office of the Village Head is approved, what will happen is the practice of corruption will continue, thereby betraying democracy and administration itself. With CDMA theory, the level of corruption can be reduced by strengthening the three elements (democracy, market, and administration) and reducing opportunities for corruption so that corruption can be reduced and the social system can work better. Meanwhile, the administration element still shows the government's weakness in managing village fund allocations which creates a fictitious village which is only used by some elements to obtain disbursement of village funds from the central government with the aim of financial misappropriation not to improve the lives of village communities.